Ecclesiology of Equality as a Critique of Social Preferentialism in the Church: An Exegetical Study of James 2:1–13 - Pasaribu Aris Samuel; Sitompul Putra Hendra S.; Nathanael Octavianus; Hutabarat Christiani; Sihombing Lince; Mariepan David (International Journal of Christian Education and Philosophical Inquiry, 2026)
The church is called to embody a community of faith characterized by love, justice, and equality before God. Nevertheless, the persistence of social favoritism within contemporary churches continues to undermine this calling and contradict the gospel's vision of an inclusive faith community. This study aims to construct an ecclesiology of equality through an exegetical analysis of James 2:1–13 as a theological response to the problem of social favoritism in the church. Employing a qualitative literature study with an exegetical-theological approach, this research examines the literary and theological message of James 2:1–13 to formulate ecclesiological principles relevant to contemporary ecclesial practice. The findings reveal that James strongly condemns favoritism as incompatible with faith in Jesus Christ and presents equality, impartiality, mercy, and the law of love as foundational principles for the life of the church. Based on these exegetical findings, the study proposes an ecclesiology of equality that envisions the church as an inclusive, participatory, just, and compassionate community that affirms the dignity of every person, particularly those who are socially and economically marginalized. In conclusion, James 2:1–13 provides a robust theological foundation for challenging social favoritism and calls the church to embody God's impartial love through equitable relationships, communal participation, and justice in its life and ministry.